Relación de las secuelas de enfermedad vascular cerebral y la depresión familiar - Guzman Aguilar, David (Universidad Michoacana de San Nicolás de Hidalgo, 2019)
The EVC is a problem with social, economic and health implications due to the disability it generates, the second world cause of death. The sequelae of EVC lie between two poles: death and complete functional recovery. With a wide range of disabilities. The dependence and care that patients require, economic burden, and environmental factors can generate depression in family members. Objective: To identify the relationship of EVC sequelae and family depression. Material and methods: Observational, descriptive, cross-sectional study, selecting Relatives of patients with sequelae of IMSS EVC, HGZ 83, from April to July 2017, the Beck Depression questionnaire was applied, and sociodemographic variables, age, occupation, socioeconomic status , time of the aftermath of EVC, schooling, family kinship. Registration Number before the Ethics and Research Committee: R-2017-1603-8. Descriptive statistics were used with mean ± standard deviation for continuous variables, for nominal qualitative frequency whith the percentage and for the correlation used chi cuadrada. Results: 104 patients, 59.6% women and 40.4% men, of the 4 relatives of patients with severe disability 3 had moderate depression, 19 with moderate-severe disability 4 of their relatives with moderate depression, 6 with mild depression and 3 with minimal depression , and of the 2 patients without significant disability the 2 normal ones. Conclusion: There is a high relationship between the sequelae of EVC with family depression (P.000). It was found that on a larger Rankin scale of the EVC, relatives and mainly the spouse had a higher degree of depression.

La EVC es un problema con implicaciones sociales, económicas y de salud por la discapacidad que genera, segunda causa mundial de muerte. Las secuelas de EVC se sitúan entre dos polos: la muerte y una recuperación funcional completa. Con una gama amplísima de discapacidades. La dependencia y cuidados que requieren los pacientes, carga económica, y factores ambientales pueden generar depresión en los familiares. Objetivo: Identificar la relación de secuelas de EVC y la depresión familiar. Material y métodos: Estudio observacional, Descriptivo, Transversal, seleccionando Familiares de pacientes con secuelas de EVC del IMSS, HGZ 83, De febrero a septiembre 2017, se aplicó el cuestionario de Depresión de Beck, y variables sociodemográficas, edad, ocupación, estado socioeconómico, tiempo de las secuelas de EVC, escolaridad, parentesco familiar. Número de Registro ante El Comité De Ética E Investigación: R-2017-1603-8. Se usó la estadística descriptiva con media ± desviación estándar para las variables continuas, para las cualitativas nominales, frecuencia con su porcentaje, y correlación se utilizó Chi cuadrada. Resultados: 104 pacientes, 59.6% mujeres y 40.4% hombres, de los 4 familiares de pacientes con discapacidad severa 3 presentaron depresión moderada, 19 con discapacidad moderada-severa 4 de sus familiares con depresión moderada, 6 con depresión leve y 3 con depresión mínima, y de los 2 pacientes sin discapacidad significativa los 2 normales. Conclusión: Existe una alta relación entre las secuelas de EVC con la depresión familiar (P.000). Se encontró que a mayor escala de Rankin del EVC, los familiares y principalmente el cónyuge presentó un mayor grado de depresión.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4313; info:eu-repo/classification/cti/3; FCMB-E-2019-0083; Depresión; Rankin; Beck